'Murundus' structures in the semi-arid region of Brazil: testing their geographical congruence with mound-building termites (Blattodea: Termitoidea: Termitidae). Issue 6 (1st November 2016) - de Souza, Henrique Jesus; Delabie, Jacques Hubert Charles
Abstract : Summary. Earth mounds called ' murundus ' are conspicuous features in the semi-arid region of Brazil, where their distribution and origin remain largely unknown. We adopted an approach based on spatially explicit mapping and modeling to determine the current and potential geographical distribution of murundus . We set up a systematic grid survey to map their current distribution using high-resolution satellite imagery available via free open source software. To obtain insights into the origin of these earth mounds, predictive models were used to test their geographical congruence with six mound-building termites (genera Cornitermes Wasmann, 1897, and Syntermes Holmgren, 1909). The Maxent algorithm was used to generate the potential distribution models based on a set of five variables related to primary environmental regimes that determine the fundamental niche of termite species. To analyze if there was some congruence between associated environmental variables, we cross-checked the results obtained from the statistical tests using MAXENT software. Murundus mostly occur in the south-central region of the Caatinga biome (i.e. seasonally dry tropical forest) in areas with moderate annual mean temperature (20–24°C) and precipitation (600–910 mm), and soils with moderate to severe constraints concerning nutrient availability. We observed a strong geographical congruence between the potential distributions of densely packed murundus and four mound-building termites [i.e. Cornitermes bequaerti Emerson, 1952, C. silvestrii Emerson, 1949, Syntermes dirus (Burmeister, 1839) and S. wheeleri (Emerson, 1925)]. Based on the significant association of those distributions with the climate and soil nutrient availability, we concluded that the formation of murundus in the semi-arid domain might be an adaptive response of mound-building termites to particular regional environmental conditions.